CLINICAL CASE: THERAPY WITH SILDENAFIL IN THE TREATMENT OF IDIOPATHIC PULMONARY HYPERTENSION - Z. S. Valieva; Z. H. Dadacheva; T. V. Martynyuk; N. M. Danilov; M. A. Saidova; I. Ye. Chazova (Евразийский Кардиологический Журнал)
The patient with the verified diagnosis of idiopathic pulmonary hypertension, negative acute vasoreactivity testing by RHC, functional class III (WHO) was treated by phosphodiesterase type 5 inhibitor sildenafil. After one year there was achieved the significant improvement of the functional and hemodynamic status.